P31 PERCUTANEOUS LEFT STELLATE GANGLION BLOCK AS PRE–TREATMENT STRATEGY FOR HIGH–RISK PATIENTS WHO ARE CANDIDATES FOR INVASIVE PROCEDURES POTENTIALLY ASSOCIATED WITH ADRENERGIC STIMULATION: AN HYPOTHESIS–GENERATING CASE REPORT. (18th May 2022) - Casula, M; Binaghi, G; Mameli, S; De Toni, C; Scotto, R; Schintu, B; Scalone, A; Tola, G; Corda, M
Abstract: Introduction: Percutaneous left stellate ganglion block (PLSGB) has been reported as a safety and effective procedure for the management of refractory arrhythmic storm (AS). In this report we present a case of a man with refractory AS effectively treated with PLSGB, subsequently candidate for an invasive procedure potentially associated with adrenergic stimulation and propose the use of this technique as pre–treatment strategy in this clinical setting. Case presentation: A 57–year–old man was admitted to our hospital for AS. Past medical history revealed that two years earlier he had been treated with primary percutaneous coronary intervention for ST–segment elevation myocardial infarction. Four months before admission he underwent coronary artery bypass graft surgery with concomitant mechanical mitral valve replacement, closure of an interventricular defect and, considering the severe left ventricular disfunction, he was implanted with an automatic defibrillator in primary prevention. At the time of admission, he was treated with lidocaine infusion with remission of arrhythmic events. Comprehensive diagnostic workup revealed no overt triggers for AS. Five days after admission, the patient experienced recurrence of ventricular arrhythmias (VA), refractory to amiodarone, lidocaine, and magnesium infusion, increased pacing rate, and sedation with dexmedetomidine. PLSGB was then attempted with the injection of lidocaine and ropivacaine using an anatomical approach with complete remission of arrhythmic events. After a week free from VAs, a new AS was observed and PLSGB was repeated using the same modality with complete arrhythmic resolution. Considering the advanced heart failure, the patient was candidate to heart transplantation (HT) and, before undergoing gastro– and colonoscopy required for inclusion in the HT program, with the aim to reduce the risk of VA recurrences triggered by potential adrenergic stimulation, we pre–treated the patient with PLSGB using only ropivacaine, with successful induction of temporary Horner syndrome (Fig. A ). The endoscopy procedures were performed successfully with no VA events and the patient was then discharged waiting for HT. Conclusion: We propose the use of PLSGB as a pre–treatment strategy for patients at high–risk of VAs who are candidates for invasive procedures potentially associated with adrenergic stimulation. This report could be hypotheses–generating for further studies on this topic.